ANALISIS PENENTUAN KOMODITAS UNGGULAN BUAH-BUAHAN DI KABUPATEN SIGI - Suryantini, Niluh Ayu; Antara, Made; Hamzens, Wildani Pingkan S. (AGROTEKBIS, 2017)
Sigi Regency, so far is to be the centre of development of horticulture in cetral Sulawesi to creat the indefendence of sociaty. This condition is needed to be the attention as the sub-sector of horticulture has the contribution in developing the agriculture in Sigi Regency. The objective of this research is in order that the people of Sigi are able to decide about which kinds of fruit can be the considered superior commodities which have the high competitive capacity in this region. So that thay can increase the welfare of the farmers. This research had beenÂ  conducted in Sigi Regency on January and February 2017. The data resourse of this research used the secondary data that was gotten from the Office of Statistic Board Centre of Central Sulawesi and Sigi Regency. The tool of Data Analysis which was used in this research was Analysis LQ (Location Quotiont). The result of this research showed that the superior commodities which there are in Sigi Regency namely; Apocado, Jackfruit, Pineaple, Papaya, Rambutan, and Rose Apple. The LQ analysis showed that there are six kinds of fruit as the considered superior commodities with the average LQ Ë 1. Avocado with the average LQ value is 5.48,Â  Jackfruit with the average LQ value is 1.04, Pineaple with the average LQ value is 1.10, Papaya with the average LQ value is 1.29, Rambutan with the average LQ value is 1.56, and Rose apple with with the average LQ value is 1.63..Key Words : Competitive Commodities, Location Quotient, Sigi Regency.